DO FIRM SIZE AND LEVERAGE AFFECT AUDIT QUALITY? EMPIRICAL FINDINGS FROM ENERGY SECTOR - Junika Halawa; Royanti Sinaga (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
Audit quality is an important element in maintaining the transparency and credibility of financial information in the capital market. The results of previous research showed inconsistent findings related to the influence of company size and leverage on audit quality, so further empirical testing is still needed. This study aims to empirically examine the influence of company size and leverage on audit quality in the energy sector, both partially and simultaneously. The research uses an explanatory quantitative approach with secondary data in the form of audited financial statements of companies listed on the Indonesia Stock Exchange for the period 2020–2024. The sampling technique uses purposive sampling. Data analysis was carried out using logistic regression with model feasibility testing through the Hosmer and Lemeshow Test, Nagelkerke R Square, Omnibus Test and multicollinearity test. The results of the study show that company size has a positive and significant effect on audit quality. Leverage also has a positive and significant effect on audit quality. Simultaneously, the size of the company and leverage had a significant effect on audit quality with the model's explainability of 60.3%. Companies with large asset sizes and high levels of leverage tend to use high-quality auditors to maintain the credibility of financial statements and meet the supervisory demands of stakeholders. This study was limited to the use of two independent variables, a specific observation period, and audit quality measurement that only used proxy affiliated with the Public Accounting Firm. Further research suggests adding other variables such as corporate governance, profitability, and business risk.